The prevalence of benign paroxysmal positional vertigo in patients with osteoporosis - Bruintjes, Tjasse D.; van der Zaag-Loonen, Hester J.; Eggelmeijer, Frank; van Leeuwen, Roeland B. (European archives of oto-rhino-laryngology, 2018)
Background Benign paroxysmal positional vertigo (BPPV) is one of the most common causes of dizziness. There is some evidence that osteoporosis is a risk factor for BPPV. Objective To determine the prevalence of BPPV in patients with proven osteoporosis. Materials and methods We examined 187 new consecutive patients who attended our osteoporosis clinic. All patients had proven osteoporosis (DEXA scan resulting in a T score ≤ − 2.5). Patients completed a screening questionnaire assessing the presence of episodic vertigo provoked by changes in head position. When we suspected the presence of BPPV, we performed a Dix–Hallpike manoeuvre and a supine roll test. If the diagnostic procedure was positive, a (therapeutic) canalith repositioning manoeuvre (CRM) was performed. Results Twelve out of 187 patients had a history of typical vertigo compatible with BPPV. In four patients, the presence of BPPV was confirmed by means of a positive Dix–Hallpike manoeuvre. The prevalence of BPPV in this population of patients with osteoporosis was 2.1% (95% CI 0.8–5.4%). Conclusion The prevalence of BPPV in patients with osteoporosis is low. Based on this study, we suggest that there does not seem to be a relation between osteoporosis and BPPV.